Placer exploration in Sri Lanka of geomorphologic investigation methods - G N Kolosova; - Gamini Soisa (RUDN Journal of Engineering Research, 2008)
Morphometric methods of evaluation of relief and river valleys in first place have been used to evaluate the territory of Shri Lanka with the search for deposits in view.